Endovascular treatment of posterior condylar canal dural arteriovenous fistula. (31st May 2016) - Maus, Volker; Söderman, Michael; Rodesch, Georges; Kabbasch, Christoph; Mpotsaris, Anastasios
Abstract : Posterior condylar canal dural arteriovenous fistulas (PCC DAVFs) are rare lesions that may present with pulse-synchronous bruit. In cases with venous reflux there is a risk of haemorrhage or even dementia. Diagnosis and endovascular treatment require a profound knowledge of the vascular anatomy of the craniocervical junction and comprehensive neurovascular imaging. We describe the clinical presentation, angiographic imaging and endovascular treatment of a PCC DAVF in a female patient with pulse-synchronous bruit as the presenting symptom. The fistula drained almost exclusively into the sigmoid sinus and internal jugular vein. There was no intracranial reflux. The PCC DAVF was treated with transvenous coil occlusion of the fistulous pouch in the condylar canal. Symptoms resolved immediately after intervention and the patient recovered quickly without any neurological deficits. MR angiography confirmed occlusion of the DAVF. The dural sinus was patent with normal blood flow.